Avaliação da contaminação microbiana em fluido para cortes de metais em indústria metalúrgica. - Costa, Cleide Caldas (2018)
Metalworking Fluids (MWF) is the class of oils and liquids used to lubricate, reduce heat and friction between the tool and parts, helping the parts machining at the time of cutting. Contamination from the dilution water and the nutrients present in the MWF can contribute to the growth of microorganisms in the fluid. These microorganisms can cause diseases in operators and also corrosion of machine components, tools and parts shortening the life of the MWF, due to the loss of its physicochemical properties. The objective of this study was to monitor the microbiological conditions of metal cutting in seven central circulation systems of a metallurgical plant. Monitoring was realized weekly for seven months. The MWF samples were analyzed for concentrations of biocidal actives N-Butyl-1,2-benzisothiazoline-3-one (NBBIT) and 1,2-benzisothiazoline-3-one (BIT) by liquid chromatography and counting of microorganisms by pour plating in specific mediums for total mesophilic aerobic bacteria, yeasts and filamentous fungi. The presence of sulfate reducing bacteria (BRS) was perform at seven weeks intervals. Bacteria and yeasts contaminated all central circulations systems and only one of the central had no BRS presence. The MWF evaluated showed no contamination by filament fungi. The concentrations of biocidal active NBBIT and BIT were below those mentioned in the literature as efficient in the control of contamination. Thus, it was concluded that the analyzed metallurgy is not following the dosage of established biocides active 200 ppm to NBBIT and 2.500 ppm to BIT, this is leading to contaminations that can be harmful to the operators. The suggestion is that the company take preventive action measures, such as weekly monitoring and corrective actions like plant audits to detect and control the microbiological load of the central circulations system.